FactCheck: do bank profits ‘belong to everyday Australians’? - Humphrey-Jenner, M.; Hodgson, Helen (The Conversation, 2018)
The Australian Banking Association says 'nearly 80% of bank profits go straight back to shareholders', the majority of whom are 'everyday Australians'. Is that right?